Kampen mellem den amerikanske præsident, Kongressen og Højesteret – styrkelsen af præsidentembedet efter 2001. - Hammer, Marie (Politik, 2010)
Former President Bush came into office convinced that the US Presidential Office had been wrongly weakened. The 2001 terrorist attack provided Bush with the opportunity to remedy this situation. Capitalised on new won public support combined with the need for the president to act in a time of emergency Bush aimed to strengthening the power of the presidential office. However, the President’s intentions at the time do not provide us with the full picture. Using agency-theory this article examines the reaction from Congress and the Supreme Court which throughout the period paved the way for change in the institutional balance of power. President Barack Obama signalled a break from this form of imperial presidency but is also dependent on enforcing his electoral pledges. Confronted by an uncooperative Congress and pressure from both Congress and the Court to investigate the Bush–era’s security policies Obama is forces to position himself in the institutional power battle.